EFEK ANTIBAKTERI EKSTRAK KULIT MANGGIS (Garcinia mangostana L) TERHADAP Staphylococcus aureus - , NUR MUPRIYUS NIAWATIN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : Staphylococcus aureus causes pneumonia 10 â 15 % of cases that is obtained from the hospital environment. Many treatments of disease caused by bacterial infection using antibiotic causes resistance, so it requires a new products that has high potential as an antibiotic. One of plants which is used more for treatment is mangosteen pericarp (Garcinia mangostana L). Objective : Knowing antibacterial effect of mangosteen pericarp extract (Garcinia mangostana L) againts Staphylococcus aureus by knowing Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). Methods : This research is experimental research using the dilution test tube method. The research design use was completely randomized design (CRD) with six treatments (the variation of extract concentration used is 100 %, 50 %, 25 %, 12,5 %, 6,25 %, and 3,125 %) , and two controls with three replications to each bacteria. Results : The Minimum Inhibitory Concentration (MIC) of mangosteen pericarp extract (Garcinia mangostana L) of Staphylococcus aureus bacteria is at concentration of 3,125 %, while the Minimum Bactericidal Concentration (MBC) of mangosteen pericarp extract of Staphylococcus aureus bacteria is at concentration of 50 %. Conclusion : Mangosteen pericarp extract (Garcinia mangostana L) has antibacterial effect againts Staphylococcus aureus.